Development and validation of the IDEAL scale for digital leadership: data from Asian schools - Hendra, Robi; Habibi, Akhmad; Md Rami, Ahmad Aizuddin; Mukminin, Amirul; Sembiring, Dian Arisandy Eka Putra; Alharmali, Turki Mesfer; Sumandya, I. Wayan (Routledge, 2026)
This study introduces the IDEAL instrument (Indonesian Digital Educational Administration Leadership) to assess digital leadership among high school principals in Indonesia. This study employed a quantitative survey approach to develop and validate the Digital Leadership Scale for high school principals in Indonesia. The process involved a series of rigorous, multi-stage steps (content validity index (CVI), exploratory factor analysis (EFA), and confirmatory factor analysis (CFA)) to ensure the scale’s validity, reliability, and contextual relevance. The results improve the validation and reliability assessment of the proposed model. The model provides a reliable, contextually relevant tool for researchers, policymakers, and practitioners.